Cerebrovascular and blood–brain barrier impairments in Huntington's disease: Potential implications for its pathophysiology. Issue 2 (9th April 2015) - Drouin‐Ouellet, Janelle; Sawiak, Stephen J.; Cisbani, Giulia; Lagacé, Marie; Kuan, Wei‐Li; Saint‐Pierre, Martine; Dury, Richard J.; Alata, Wael; St‐Amour, Isabelle; Mason, Sarah L.; Calon, Frédéric; Lacroix, Steve; et al.
<x xml:space="preserve">Abstract</x> Objective Although the underlying cause of Huntington's disease (HD) is well established, the actual pathophysiological processes involved remain to be fully elucidated. In other proteinopathies such as Alzheimer's and Parkinson's diseases, there is evidence for impairments of the cerebral vasculature as well as the blood–brain barrier (BBB), which have been suggested to contribute to their pathophysiology. We investigated whether similar changes are also present in HD. Methods We used 3‐ and 7‐Tesla magnetic resonance imaging as well as postmortem tissue analyses to assess blood vessel impairments in HD patients. Our findings were further investigated in the R6/2 mouse model using in situ cerebral perfusion, histological analysis, Western blotting, as well as transmission and scanning electron microscopy. Results We found mutant huntingtin protein (mHtt) aggregates to be present in all major components of the neurovascular unit of both R6/2 mice and HD patients. This was accompanied by an increase in blood vessel density, a reduction in blood vessel diameter, as well as BBB leakage in the striatum of R6/2 mice, which correlated with a reduced expression of tight junction‐associated proteins and increased numbers of transcytotic vesicles, which occasionally contained mHtt aggregates. We confirmed the existence of similar vascular and BBB changes in HD patients. Interpretation Taken together, our results provide evidence for alterations in the cerebral vasculature in HD leading to BBB leakage, both in the R6/2 mouse model and in HD patients, a phenomenon that may, in turn, have important pathophysiological implications. Ann Neurol 2015;78:160–177